The charge transport and photoconduction mechanisms of TiO 2-based dye sensitized solar cell - Farooq, W.A.; Fatehmulla, Amanullah; Ocakoglu, K.; Yakuphanoğlu, Fahrettin (My University, 2012)
The charge transport and photoconduction mechanisms of the TiO 2-based DSSC were analyzed under dark and illumination conditions. The effects of high and low electric fields on charge transport mechanism of the solar cell were investigated by current-voltage characteristics. It was found that the charge transport mechanism of the solar cell was controlled by the thermionic emission (TEC)) at lower voltage and followed by space charge limited current (SCLC) at the higher voltages. The photovoltaic parameters of the solar cell were determined. It is evaluated that the charge transport mechanism is controlled by TEC and SCLC mechanisms, while photoconduction is controlled by supralinear recombination mechanism. © 2012 IEEE.
2012 9th International Conference on High Capacity Optical Networks and Enabling Technologies, HONET 2012 -- 14 December 2012 through 14 December 2012 -- Istanbul -- 95760
Keywords: impedance spectroscopy; Photovoltaic properties; TiO2 photoanode